The progress of molecules and strategies for the treatment of HBV infection - Pan, Youlu; Xia, Heye; He, Yanwen; Zeng, Shenxin; Shen, Zhengrong; Huang, Wenhai (Frontiers in Cellular and Infection Microbiology, 2023)
Hepatitis B virus infections have always been associated with high levels of mortality. In 2019, hepatitis B virus (HBV)-related diseases resulted in approximately 555,000 deaths globally. In view of its high lethality, the treatment of HBV infections has always presented a huge challenge. The World Health Organization (WHO) came up with ambitious targets for the elimination of hepatitis B as a major public health threat by 2030. To accomplish this goal, one of the WHO’s strategies is to develop curative treatments for HBV infections. Current treatments in a clinical setting included 1 year of pegylated interferon alpha (PEG-IFNα) and long-term nucleoside analogues (NAs). Although both treatments have demonstrated outstanding antiviral effects, it has been difficult to develop a cure for HBV. The reason for this is that covalently closed circular DNA (cccDNA), integrated HBV DNA, the high viral burden, and the impaired host immune responses all hinder the development of a cure for HBV. To overcome these problems, there are clinical trials on a number of antiviral molecules being carried out, all -showing promising results so far. In this review, we summarize the functions and mechanisms of action of various synthetic molecules, natural products, traditional Chinese herbal medicines, as clustered regularly interspaced short palindromic repeats and their associated proteins (CRISPR/Cas)-based systems, zinc finger nucleases (ZFNs), and transcription activator-like effector nucleases (TALENs), all of which could destroy the stability of the HBV life cycle. In addition, we discuss the functions of immune modulators, which can enhance or activate the host immune system, as well some representative natural products with anti-HBV effects.